A delayed Tenzel flap - Francesca Falcinelli; Giovanni Rubegni; Ernesto De Piano (PAGEPress Publications, 2024)
A 71-year-old man presented with a lentigo maligna melanoma (Breslow 0.25 mm) of the left lower eyelid. Complete excision was achieved after 3 Slow Mohs stages, resulting in a quadrangular 1.8x1.2 cm full-thickness defect. After the first stage, upper and lateral margins resulted as histologically infiltrated. Therefore, an additional lateral strip was taken after 3 days, resulting in a tumor-free result. Radicalization was completed after another 8 days on the posterior lamella and rim with immediate reconstruction.